Advances in the role of microRNAs associated with the PI3K/AKT signaling pathway in lung cancer - Wang, Yanting; Zhang, Tao; He, Xin (Frontiers in Oncology, 2023)
Cancer has long been a topic of great interest in society and a major factor affecting human health. Breast, prostate, lung, and colorectal cancers are the top four tumor types with the greatest incidence rates in 2020, according to the most recent data on global cancer incidence. Among these, lung cancer had the highest fatality rate. Extensive research has shown that microRNAs, through different signaling pathways, play crucial roles in cancer development. It is considered that the PI3K/AKT signaling pathway plays a significant role in the development of lung cancer. MicroRNAs can act as a tumor suppressor or an oncogene by altering the expression of important proteins in this pathway, such as PTEN and AKT. In order to improve the clinical translational benefit of microRNAs in lung cancer research, we have generalized and summarized the way of action of microRNAs linked with the PI3/AKT signaling pathway in this review through literature search and data analysis.